High Prevalence of Drug Resistance and Class 1 Integrons in Escherichia coli Isolated From River Yamuna, India: A Serious Public Health Risk - Singh, Nambram Somendro; Singhal, Neelja; Kumar, Manish; Virdi, Jugsharan Singh (Frontiers in Microbiology, 2021)
Globally, urban water bodies have emerged as an environmental reservoir of antimicrobial resistance (AMR) genes because resistant bacteria residing here might easily disseminate these traits to other waterborne pathogens. In the present study, we have investigated the AMR phenotypes, prevalent plasmid-mediated AMR genes and integrons in commensal strains of Escherichia coli, the predominant fecal indicator bacteria isolated from a major urban river of northern India Yamuna. The genetic environment of blaCTX-M-15 was also investigated. Our results indicated that 57.5% of the E. coli strains were resistant for at least two antibiotic classes and 20% strains were multi drug resistant i.e resistant for three or more antibiotic classes. The multiple antibiotic resistance index of about one-third of the E. coli strains was quiet high (>0.2) reflecting high contamination of river Yamuna with antibiotics. With regards to plasmid-mediated AMR genes, blaTEM-1 was present in 95% of the strains followed by qnrS1 and armA (17% each), blaCTX-M-15 (15%), strA-strB (12%) and tetA (7%). Contrary, to the earlier reports where blaCTX-M-15 was mostly associated with pathogenic phylogroup B2, our study revealed that CTX-M-15 type ESBLs were present in the commensal phylogroups A and B1, also. The genetic organization of blaCTX-M-15 was similar to that reported for E. coli, isolated from other parts of the world and ISEcp1 was present upstream of blaCTX-M-15. The integrons of classes 2 and 3 were absent but class 1 integron gene intI1 was present in 75% of the isolates denoting its high prevalence in E. coli of river Yamuna. These evidences indicate that due to high prevalence of plasmid-mediated AMR genes and intI1, commensal E. coli can become vehicles for widespread dissemination of AMR in the environment. Thus, regular surveillance and management of urban rivers is necessary to curtail the spread of AMR and associated health risks.